Peculiarities of PED virus pathogenesis in neonatal non-immune piglets on Ukraine farms - Masjuk, D.; Masiuk, Dmytro; Masiuk, D. N.; Masiuk, D. M.; Masiuk, D.; Masyuk, D. N.; Masyuk, D. M.; Masyuk, D.; Масюк, Дмитро Миколайович; Nedzvetsky, V. S.; Недзвецький, Віктор Станіславович; Sosnitskyi, O.; et al. (Oles Honchar Dnipro National University, 2018)
The article presents the results of study of the immune and tissue features of pathogenesis of PED virus in neonatal piglets in Ukraine. Clinical and epizootological analysis was performed in three separate agricultural enterprises with adverse epidemiological situation with PED virus. Blood samples and fragments of the small intestine of PEDv infected piglets were used to study the characteristics of the pathogenesis of PED virus. It has been determined that the pathogenesis of super-acute infection by the PED virus in 1–7 day old non-immune piglets proceeds according to the classic type of infectious process with a relay transmission of the pathogen. Moreover, diarrhea syndrome has induced the development of irreversible and lethal pathophysiological lesions by replication the PED virus in enterocytes of infected piglets. Pathogenetic changes observed in PEDv infected piglets were combined with the following components: acute inflammatory-necrotic process in the tissue of the intestine, destruction and desquamation of the epithelium of the small intestine. The infection process on day 3–5 of manifestation of clinical signs of PED virus is accompanied with an increase in the number of erythrocytes, leukocytes and monocytes, hemoglobin, hematocrit level and aminotransferase activity. In addition, PED virus infection induced an increase in IgM levels and the number of phagocytizing leukocytes with increased aggressiveness and digestive power. The duration of the release of PED virus with feces is 26–37 days after cessation of watery diarrhea. The concentration of PEDv in the feces of convalescent piglets ranged from 120 to 1700 equivalent genome in 1 g of tissue. Parasite coenotic associations of the microbiocenosis of the digestive tract of PED virus infected piglets did not have time to form into stable epitopes. There was a constant quantitative prevalence of transient microbiota and a decrease in the share of probiotic microorganisms. The intestinal microflora consists of random transient microbiota of the environment with pathogenic properties. The results presented show evidence that molecular and cell-mediated immunological events in non-immune piglets have the initial stage of the specific progress of immune response against PEDv. У статті представлені результати вивчення імунних та тканинних особливостей патогенезу вірусу ЕДС у новонароджених поросят в Україні. Клініко-епізоотологічний аналіз проводився у трьох окремих сільськогосподарських підприємствах з несприятливою епідеміологічною ситуацією за вірусом ЕДС. Зразки крові та фрагменти тонкої кишки інфікованих поросят використовували для вивчення особливостей патогенезу вірусу ЕДС. Встановлено, що патогенез над-гострої інфекції вірусом ЕДС у 1–7-денних неімунних поросятах протікає за класичним типом інфекційного процесу з естафетною передачею збудника. Крім того, синдром діареї індукував розвиток необоротних і летальних патофізіологічних уражень шляхом реплікації вірусу ЕДС в ентероцитах інфікованих поросят. Патогенетичні зміни, що спостерігаються у інфікованих поросят, об'єднувалися з наступними компонентами: гострим запально-некротичним процесом в тканині кишечника, деструкцією і десквамацією епітелію тонкої кишки. Процес інфікування на 3–5-й день прояву клінічних ознак ЕДС супроводжується збільшенням кількості еритроцитів, лейкоцитів і моноцитів, гемоглобіну, рівня гематокриту і амінотрансферазної активності. Крім того, інфекція ЕДС індукувала збільшення рівня IgM і кількості фагоцитуючих лейкоцитів з підвищеною агресивністю і властивостями травлення. Тривалість вивільнення вірусу ЕДС з фекаліями становить 26–37 днів після припинення водянистої діареї. Концентрація вірусу ЕДС у фекаліях реконвалесцентних поросят становила від 120 до 1700 шеном-еквівалентів в 1 г матеріалу. Паразитоценотичні асоціації мікробіоценозу шлунково-кишкового тракту інфікованих вірусом ЕДС поросят не встигли сформуватися у стабільні епітопи. Спостерігалася постійна кількісна поширеність транзитарної мікробіоти і зменшення частки пробіотичних мікроорганізмів. Мікрофлора кишечника складається з випадкової транзитарної мікробіоти середовища з патогенними властивостями. Наведені результати свідчать про те, що молекулярні та клітинно-опосередковані імунологічні події у неімунних поросят мають початкову стадію специфічного прогресу імунної відповіді проти вірусу ЕДС.
Особливості патогенезу вірусу ЕДС у неонатальних неімунних поросят на фермах України
Особенности патогенеза вируса ЭДС у неиммунных неиммунных поросят на фермах Украины
Масюк Дмитро Миколайович https://orcid.org0000-0002-2800-2580 Недзвецький Віктор Станіславович https://orcid.org/0000-0001-8975-6952 Сосницький Олександр Іванович https://orcid.org/0000-0002-2853-9732 Кокарєв Андрій Вікторович https://orcid.org/0000-0002-5673-5984
Keywords: intestinal microbiocenosis; кишковий мікробіоценоз; PEDv; вірус ЕДС; pathogenesis; патогенез; piglets; поросята; morphological and biochemical indicators of blood; морфологічні та біохімічні показники крові; cell-mediated immunity; клітинний імунітет; humoral immunity; гуморальний імунітет